IDENTIFIKASI TARGET RESEPTOR SENYAWA 10,11-DIHIDROERISODIN SEBAGAI KANDIDAT ANTIKANKER SECARA IN SILICO - Endah, Srie Rezeki Nur (STIKes Bakti Tunas Husada, 2018)
Cancer is one of the most feared diseases and is considered the leading cause of death worldwide. Generally, cancer drugs are synthetic drugs with relatively more expensive prices and have harmful side effects, so many people turn to traditional medicine, for example by utilizing herbal medicine. Erythrina poeppigiana is one of the plants that can be used as a medicinal plant containing 10.11-dihidroerisodin compounds that are useful anticancer etnofarmakologi. The purpose of this study was to identify the target of 10,11 dihydroerisodin receptor compound as an insertiico anticancer candidate. The pure isolate was then tested physicochemically MS, UV-Vis, IR, 13C-NMR, 1H-NMR, to obtain the structure of 10.11-dihydroerisodin alkaloid compound which then to target receptors in silico. From the results of the study it was found that 10.11-dihydroerisodin compound can work on the Serine / threonine-protein kinase Chk1 receptor that serves as an anti-cancer candidate.Â Keywords : 10,11-dihidroerisodin, anti-cancer, target receptors